MODELING OF ADS-B MESSAGES TRANSMISSION THROUGH SATELLITE TELECOMMUNICATION CHANNEL IRIDIUM USING NETCRACKER PROFESSIONAL 4.1 - Харченко, В.; Барабанов, Ю.; Грехов, A.; Іваненко, М.; Лобанов, Р. (Proceedings of National Aviation University, 2012)
The model for the traffic analysis in a communication channel "aircraft - satellite - ground station" wasbuilt and used for modeling of transfer ADS-B messages with the help low-orbit satellite complex Іrіdіum.Dependences of factor BER on channel average working load and average utilization time were obtained.Dependences of package failure probabilities on average working load, average utilization time and signaltraveling time were analyzed. The developed model was applied for determination of traffic characteristics ina communication channel "aircraft - satellite - ground station": the dependence of average working load,average channel utilization time and message traveling time on the size of transaction, the dependence oftravelling time on channel delay time were built.